APPLICATION OF THE JIGSAW LEARNING MODEL TO THE LEARNING OUTCOMES OF HISTORY OF XI GRADE STUDENTS AT SMA NEGERI 4 LUBUKLINGGAU - Yaswan Rilau Nisas, Yeni Asmara, Agus Susilo (JURNAL EDUSCIENCE, 2023)
The aim of this study was to find out if the application of the Jigsaw learning model could significantly improve the results of learning history for class XI students at SMA Negeri 4 Lubuklinggau. At this time it is very important for the world of education to continue to improve its ability to teach with the latest learning models so that the teaching and learning process is not boring. The method used in this study is quantitative with a quasi-experimental approach. The population of this study were all of class VII, totaling 265 students and the sample taken in this study was class XI MIA 4, totaling 32 students. Samples were taken by simple random sampling. The conclusion from this study is whether there is a significant increase in the results of studying history in class XI SMA Negeri 4 Lubuklinggau after being given learning using the Jigsaw learning model. This can be seen from the results of the analysis with the t-test obtained t-count> ttable (7.20> 2.567) this means that H0 is rejected Ha is accepted. From the research that has been carried out by researchers, it is clear that the application of the Jigsaw learning model can improve the learning outcomes of class XI students at SMA Negeri 4 Lubuklinggau. These results are in accordance with the research objectives so that learning outcomes continue to increase and become an alternative for teachers in the future to continue to innovate.Keywords: Application, Jigsaw learning model, Learning OutcomesÂ AbstrakPenelitian ini bertujuan untuk mengetahui apakah penerapan model pembelajaran Jigsaw dapat meningkatkan hasil belajar sejarah siswa kelas XI SMA Negeri 4 Lubuklinggau secara signifikan. Pada saat ini sangat penting bagi dunia pendidikan untuk terus meningkatkan kemampuannya dalam mengajar dengan model pembelajaran terbaru agar proses belajar mengajar tidak membosankan. Metode yang digunakan dalam penelitian ini adalah kuantitatif dengan pendekatan eksperimen semu. Populasi penelitian ini adalah seluruh siswa kelas VII yang berjumlah 265 siswa dan sampel yang diambil dalam penelitian ini adalah kelas XI MIA 4 yang berjumlah 32 siswa. Sampel diambil dengan simple random sampling. Kesimpulan dari penelitian ini adalah adakah peningkatan hasil belajar sejarah yang signifikan pada siswa kelas XI SMA Negeri 4 Lubuklinggau setelah diberikan pembelajaran dengan model pembelajaran Jigsaw. Hal ini terlihat dari hasil analisis dengan uji t diperoleh thitung > ttabel (7,20 > 2,567) hal ini berarti H0 ditolak Ha diterima. Dari penelitian yang telah dilakukan peneliti, terlihat bahwa penerapan model pembelajaran Jigsaw dapat meningkatkan hasil belajar siswa kelas XI SMA Negeri 4 Lubuklinggau. Hasil tersebut sesuai dengan tujuan penelitian agar hasil belajar terus meningkat dan menjadi alternatif bagi guru ke depan untuk terus berinovasi.Kata kunci : Penerapan, model pembelajaran Jigsaw, Hasil Belajar